OBITUARY: IN MEMORY OF PROFESSOR EIKE W. SCHAMP (1941–2019) - Stryjakiewicz, Tadeusz (Quaestiones Geographicae, 2019)
Professor Eike W. Schamp, an eminent German economic geographer, died of a serious illness on 8 February 2019. For many years he was director of the Institute of Economic and Social Geography and dean of the Faculty of Geographical Sciences at the Johann Wolfgang Goethe University in Frankfurt am Main. He was also a full member of industrial commissions of the International Geographical Union and constantly cooperated with our journal.